2017
DOI: 10.1007/s10147-016-1086-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intraoperative radiotherapy in the treatment of retroperitoneal sarcoma

Abstract: IORT was used infrequently for RPS but generated equivalent outcomes compared to EBRT, despite being utilized more often for larger tumors and those with peri-tumoral soft-tissue invasion. Patients with the most common subtype (liposarcoma) may benefit from combination IORT with adjuvant EBRT versus other regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Retroperitoneal sarcoma does not have a good prognosis. In studies, 5 year local control is 50% and 10 year survival is about 5% (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Retroperitoneal sarcoma does not have a good prognosis. In studies, 5 year local control is 50% and 10 year survival is about 5% (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 14 included studies reporting on 3 nationally recognised central databases, one was from Canada and the USA 25 and the others were all from the USA [26][27][28][29][30][31][32][33][34][35][36][37][38] (Table 1). Six studies used The Surveillance, Epidemiology and End Results (SEER) database [25][26][27][28][29][30], five studies reported from the United States National Cancer Data Base (US NCDB) [31][32][33][34][35] and the final three used the American College of Surgeons' National Surgical Quality Improvement Program (ACS NSQIP) [36][37][38]. The 14 studies span over four decades of surgical treatment for retroperitoneal sarcomas, with the earliest studies reporting data from 1973 [25,28] and the most recent from 2015 [31].…”
Section: Demographics Of Included Studiesmentioning
confidence: 99%
“…Studies from the SEER and US NCDB databases did not report 30-day morbidity rates [25][26][27][28][29][30][31][32][33][34][35]. However, Ecker et al did report a hospital readmission rate within 30-days of 6.9% for the neo-adjuvant radiotherapy group (12/174 patients) and 6.3% for the surgery alone group (120/1 908 patients), with no statistical difference [32].…”
Section: -Day Morbidity and Mortalitymentioning
confidence: 99%
See 2 more Smart Citations